Contextualizing Conques. Imaginaries, Narratives & Geographies - Foletti, Ivan; Hahn, Cynthia; Racaniello, Kris N.; Voyer, Cécile; Palladino, Adrien (Brepols, 2023)
Reapproaching Conques from new contexts is the basis of the present volume, a product of the international project “Conques in the Global World. Transferring Knowledge: from Material to Immaterial Heritage” (Marie Skłodowska-Curie Research and Innovation Staff Exchange H2020). Although it is an important location of cultural heritage and has been consequential historiographically and in the formation of art history, there has never been a comprehensive, interdisciplinary approach to this momentous site. Thus, this volume publishes the first results of the interdisciplinary and international project, which were initially presented at a conference and enriched by workshops held in New York City in the summer of 2022. The collected essays open with reflective and historiographic work on Conques in the nineteenth century. These segue into essays reconsidering specific integral elements of extant medieval materials at the site. Finally, the volume concludes with a series of essays devoted to placing Conques in a broader context. The entire volume aims to open to as yet unaddressed questions in scholarship on Conques, with the hope that this work will provide a foundation for future studies.